Pengaruh Temperatur Udara Terhadap Kinerja Tungku Gasifikasi Tipe Downdraft Continue Dengan Pengisian Ulang 2 Kali - Rhoshid, Muhammad Ismail Al; , Ir. Subroto, MT; , Ir. Sartono Putro, MT (2016)
Biomass is one of alternative energy to replace fossil fuels (petroleum) that are renewable, for example, is rice husk. But in everyday life only rice husks used as an ingredient to help the process of burning bricks or simply dumped without further utilized, therefore the further processing of rice husk to be more efficient. One of them is the method of gasification. The purpose of this study was to determine the effect of air temperature on the combustion temperature, ignition time and time effective flame-fired furnace gasification of rice husk. This study uses a type of downdraft gasification furnace which means the direction of air flow and the direction of gas gasification is down. The study was conducted by varying the temperature of the incoming air into the gasification furnace with variations in air temperature 40°C, 50°C and 60°C and then retrieve data that includes combustion temperatures, ignition timing and effective burning time. The results showed variations in air temperature affect the combustion temperature, ignition time and time effective flame furnace produced. At an air temperature of 40°C on average the highest combustion temperature of 547,1°C Ignition time 7 minutes and time effective flame for 53 minutes. Air temperature 50°C on average the highest combustion temperature of 553,6°C Ignition time 6 minutes and time effective flame for 50 minutes. While the air temperature of 60°C average the highest combustion temperature of 549,1°C ignition timing 5 minutes and time effective flame for 42 minutes.